2020
DOI: 10.3390/plants9010119
|View full text |Cite
|
Sign up to set email alerts
|

Citrus limon (Lemon) Phenomenon—A Review of the Chemistry, Pharmacological Properties, Applications in the Modern Pharmaceutical, Food, and Cosmetics Industries, and Biotechnological Studies

Abstract: This review presents important botanical, chemical and pharmacological characteristics of Citrus limon (lemon)—a species with valuable pharmaceutical, cosmetic and culinary (healthy food) properties. A short description of the genus Citrus is followed by information on the chemical composition, metabolomic studies and biological activities of the main raw materials obtained from C. limon (fruit extract, juice, essential oil). The valuable biological activity of C. limon is determined by its high content of phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
187
1
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(212 citation statements)
references
References 67 publications
(136 reference statements)
7
187
1
17
Order By: Relevance
“…Currently, there are limited studies on lemon seeds, focusing only on the extraction of oil from the seeds, and there are few studies on the biological activity and its components. 1,2 Many types of avonoids can be extracted from natural plants, most of which possess biological activity. Modern molecular biological methods have been used to prove that the avonoids extracted from plants have certain anti-oxidant, antihypertensive, anti-inammatory, and anti-cancer effects.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are limited studies on lemon seeds, focusing only on the extraction of oil from the seeds, and there are few studies on the biological activity and its components. 1,2 Many types of avonoids can be extracted from natural plants, most of which possess biological activity. Modern molecular biological methods have been used to prove that the avonoids extracted from plants have certain anti-oxidant, antihypertensive, anti-inammatory, and anti-cancer effects.…”
Section: Introductionmentioning
confidence: 99%
“…491-71-4; Figure 4 A) exhibited the strongest inhibitory activity (97.0 ± 2.20%). Chrysoeriol is present in lemon, Rooibos tea, pepper, and green vegetables such as celery, and exerts antioxidant, anti-inflammatory, and antitumor effects [ 41 , 42 , 43 , 44 , 45 ]. It has been reported that chrysoeriol inhibits CYP1B1 enzyme activity responsible for hydroxylation of 17β-estradiol in MCF-7 breast cancer cells [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chrysoeriol is present in several foods and vegetables [ 41 , 42 , 43 , 44 , 45 ]. Many dietary phenolics are generally poorly bioavailable, limiting their distribution in systemic tissues of their native form, mainly as glycosides and complex oligomeric structures [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, different terpenoids mainly present in EOs (monoterpenes such as citral, pinene, or terpinene, as well as poly(methoxyflavones) and furanocoumarins), have been used since ancient times to treat a variety of health diseases, such as spasms, fever, respiratory problems, cardiovascular diseases, gastrointestinal problems or anxiety [ 5 ]. Several works have demonstrated the antimicrobial performance of EOs against pathogenic bacteria and fungus strains [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%